PKM (Pengabdian Kepada Masyarakat) Upaya Pencegahan Covid 19 Di Area Mesjid/ Musholla Di Lingkungan Ujung Gurap Kota Padangsidimpuan - Napitupulu, Natar Fitri (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2020)
Community Service (PKM) carried out in this manuscript is the whole community. The virus that causes Coronavirus Disease 2019 (COVID-19) is mainly transmitted through droplets (saliva splashes) produced when an infected person coughs, sneezes, or exhales. These droplets are too heavy and cannot stay in the air, so they quickly fall and stick to the floor or other surface. We can get infected when we breathe air that contains the virus if we are too close to people who are already infected with COVID-19 (WHO, 2020). As an effort to end the COVID-19 pandemic, the COVID-19 Handling Task Force invites all people to be at the forefront by implementing 3 steps (wearing masks, maintaining distance and washing hands. This counseling is carried out to all members of the community to break the chain of transmission of Covid-19 in the Ujung Gurap neighborhood Padangsidimpuan City and carried out for one day using posters, leaflets and evaluations were carried out using a check list with an evaluation assessment through the process and results of counseling that all residents carried out the Health Protocol.